Plasmonic near-touching titanium oxide nanoparticles to realize solar energy harvesting and effective local heating. Issue 16 (12th April 2016) - Yan, Jiahao; Liu, Pu; Ma, Churong; Lin, Zhaoyong; Yang, Guowei
Abstract : Heavily doped titanium oxide as a new type of plasmonic material to realize light absorption and local heating. Abstract : Through the excitation of plasmon resonance, the energy of plasmonic nanoparticles either reradiates through light scattering or decays into energetic electrons (absorption). The plasmon-induced absorption can greatly enhance the efficiency of solar energy harvesting, local heating, photodetection and photocatalysis. Here, we demonstrate that heavily self-doped titanium oxide nanoparticles (TiO1.67 analogue arising from oxygen vacancies in rutile TiO2 ) with the plasmon resonance dominated by an interband transition shows strong absorption to build a broadband perfect absorber in the wavelength range from 300 to 2000 nm covering the solar irradiation spectrum completely. The absorptivity of the fabricated array is greater than 90% in the whole spectral range. And the broadband and strong absorption is due to the plasmon hybridization and hot spot generation from near-touching TiO1.67 nanoparticles with different sizes. What is more, the local heating of a TiO1.67 nanoparticle layer is fast and effective. The temperature increases quickly from 30 °C to 80 °C within 200 seconds. This local heating can realize rapid solar-enabled evaporation which can find applications in large-scale distillation and seawater desalination. These findings actually open a pathway for applications of these newly developed plasmonic materials in the energy and environment fields.